First record of the ghost bat Diclidurus scutatus Peters (Mammalia, Chiroptera, Emballonuridae) in São Paulo city, Brazil - Sodré, Miriam M.; Uieda, Wilson [UNESP] (Sociedade Brasileira de Zoologia, 2006)
Devido aos seus hábitos de voar alto e se abrigar em folhas de palmeiras, há poucos registros na literatura sobre o morcego Diclidurus scutatus Peters, 1869. No Brasil, essa espécie é conhecida somente na região Norte e o presente estudo descreve sua primeira ocorrência na região Sudeste. O morcego foi encontrado morto no parapeito da janela de um apartamento do nono andar, em um edifício residencial, na área urbana da cidade de São Paulo, estado de São Paulo. Provavelmente esse morcego devia viver na Serra da Cantareira, um fragmento da mata Atlântica, próximo da cidade de São Paulo.

Because of their habits (fly high and harbor on palm leaves), there are few records of the ghost bat Diclidurus scutatus Peters, 1869. In Brazil, this species is known only from Northern region and this paper describes its first occurrence in Southeastern region. The ghost bat was found died on the window sill of a 9th floor apartment of a residential building in the urban area in the city of São Paulo, São Paulo State. Probably this bat must live at Serra da Cantareira, one of the Atlantic forest fragment nearby São Paulo city.
Primeiro relato do morcego-fantasma Diclidurus scutatus Peters (Mammalia, Chiroptera, Emballonuridae) na cidade de São Paulo, Brasil
Keywords: Área urbana; morcego insetívoro; Insectivorous bat; urban area